2008
DOI: 10.4161/auto.5782
|View full text |Cite
|
Sign up to set email alerts
|

Eating on the fly: Function and regulation of autophagy during cell growth, survival and death in Drosophila

Abstract: Significant progress has been made over recent years in defining the normal progression and regulation of autophagy, particularly in cultured mammalian cells and yeast model systems. However, apart from a few notable exceptions, our understanding of the physiological roles of autophagy has lagged behind these advances, and identification of components and features of autophagy unique to higher eukaryotes also remains a challenge. In this review we describe recent insights into the roles and control mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 61 publications
1
43
0
Order By: Relevance
“…Genes encoding transcription factors, caspases, Atg genes, and regulators of growth have been identified that are required for proper destruction of larval salivary glands (25). In addition, hundreds of genes are induced within 4 h of salivary gland degradation (26), suggesting that additional genes may function in the death of these cells.…”
Section: Resultsmentioning
confidence: 99%
“…Genes encoding transcription factors, caspases, Atg genes, and regulators of growth have been identified that are required for proper destruction of larval salivary glands (25). In addition, hundreds of genes are induced within 4 h of salivary gland degradation (26), suggesting that additional genes may function in the death of these cells.…”
Section: Resultsmentioning
confidence: 99%
“…29,34 Western blot analysis of Drosophila samples from different fasting and developmental conditions, shows Ref(2)P and ubiquitin profiles change dramatically at times consistent with activation of autophagy. 35,[65][66][67] In terms of inclusion body or aggregate formation, we identified two exceptions. The first is that the soluble and insoluble profiles of both markers increase at a time when hormonally triggered autophagy is occurring (Sup.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…Following this eating period, larvae crawl out of the food, fasting for several hours before initiating pupation. At this time, autophagy (destruction of cellular components to garner nutrients) is activated in the fat body (40,41). To test whether Df[dilp1-5] animals display starvation responses while actively eating, lysotracker was used to monitor activation of autophagy.…”
Section: Dilp1-5 Function Than Is Fertility and Development Of Eggs Tmentioning
confidence: 99%